HUBUNGAN PREFERENSI MAKANAN ASRAMA DAN KONSUMSI PANGAN DENGAN STATUS GIZI MAHASISWA/I JURUSAN KEPERAWATAN POLITEKNIK KESEHATAN MEDAN TAHUN 2014 - Tinah, Tinah (Jurnal Mutiara Kesehatan Masyarakat, 2017)
Indonesia’s IPM (Human Development Index) was 0.617 and ranks the 124th of 187 countries. Human resources that need to be paid attention are teenagers. On this occasion, teenagers need to consume enough food since the food which is consumed in adolescence age will affect their health in the next phase of their life; that is, when they are adults and old people. Some factors which influence nutrition status are food consumption and the incidence of infection. The objective of the research was to find out the correlation of dormitory food preference and food consumption with nutrition status of the students at the Nursing Department of Politeknik Kesehatan Medan, in 2014. The research used observational quantitative approach with cross sectional study. The population was 350 students who studied at the Nursing Department of Politeknik Kesehatan Medan, and 99 of them were used as the samples, taken by using proportional random sampling technique. The data were gathered by conducting observation and interviews with questionnaires and analyzed descriptively on all variables of dormitory food preference and food consumption  with students’ nutrition status by using path analysis at α = 5%. The result of the research showed that 70% of the respondents did not like the food in the dormitory. The result of path analysis, using linear regression test, showed that there were direct preference correlation with nutrition status at 0.061 and indirect preference correlation with nutrition status through the level of energy adequacy at 0.07 which indicated that preference could directly correlate without being through the level of energy adequacy. It is recommended that the food provider at the Nursing Department of Politeknik Kesehatan Medan provide qualified food in dormitory. Food processing should meet recipe standard, portion standard, and ingredient standard so the taste of food served in dormitory will be good and the students’ nutrition status will improve.  Keywords: Preference, Food Consumption, Nutrition Status